2002
DOI: 10.1007/s00122-002-0949-6
|View full text |Cite
|
Sign up to set email alerts
|

Microsynteny between the Medicago truncatula SYM2-orthologous genomic region and another region located on the same chromosome arm

Abstract: A synteny based positional cloning approach was started to clone the pea SYM2 gene by using locally conserved genome structure with the model plant Medicago truncatula. We reported that a pea marker tightly linked to SYM2 was used to screen a M. truncatula BAC library, and two contigs named C1/C2 and C3 were constructed that are both located on the long arm of M. truncatula chromosome 5 and separated by 9 cM. C1/C2 is highly microsyntenic to the pea SYM2 genomic region and corresponds to the M. truncatula SYM2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Species of Buchnera and Corynebacterium have low levels of chromosomal rearrangements and lack recA and recBCD orthologs, respectively [ 8 , 9 ], thus suggesting that recombination is an important factor for loss of synteny. Synteny studies have focused in short gene clusters in eukaryotes [ 10 , 11 ] while whole chromosome comparative analysis has been done in bacteria and archaea [ 12 - 18 ]. For example, there is a striking conservation between the chromosomes of Escherichia coli and Salmonella typhimurium [ 19 ], and also between those of Brucella melitensis, B. suis and Mesorhizobium loti [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Species of Buchnera and Corynebacterium have low levels of chromosomal rearrangements and lack recA and recBCD orthologs, respectively [ 8 , 9 ], thus suggesting that recombination is an important factor for loss of synteny. Synteny studies have focused in short gene clusters in eukaryotes [ 10 , 11 ] while whole chromosome comparative analysis has been done in bacteria and archaea [ 12 - 18 ]. For example, there is a striking conservation between the chromosomes of Escherichia coli and Salmonella typhimurium [ 19 ], and also between those of Brucella melitensis, B. suis and Mesorhizobium loti [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is, however, evidence of gene duplication in Medicago; glutathione synthetase exists in two copies, most likely through a tandem duplication (Frendo et al, 2001). Additionally, Medicago chromosome 5 exhibits orthology with another region on the same chromosome showing evidence of segmental duplication (Gualtieri and Bisseling, 2002). It has been suggested that Medicago has a simple genome structure, with only tandem and segmental duplications (Kulikova et al, 2001).…”
Section: Evolutionary History Of Legumes and Grassesmentioning
confidence: 99%